2022
DOI: 10.1177/08862605221080137
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Intimate Partner Violence and Suicidal Ideation Among Female and Male Adults in South Korea: A Nationally Representative Longitudinal Study

Abstract: This study sought to assess the prevalence of intimate partner violence (IPV) victimization and to examine the sex-stratified associations between IPV and suicidal ideation in South Korea. This study used nationally representative longitudinal survey data from 2011 to 2020 of the Korean Welfare Panel Study of 9732 married adults at baseline. Participants were annually asked about IPV experiences of verbal abuse, physical threat, or physical assault over the past year in 2011–2019. Suicidal ideation in the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Finally, it is notable that men made up more than one-fourth of this cohort of multimorbid individuals reporting IPV victimization, suicidality, and depression. These findings provide support for research involving men showing links between IPV victimization and suicidality [11,16] but are in contrast to the studies that found no link among men between suicidality and IPV victimization [14,15] and an inverse relationship between IPV and depression [15]. Perhaps the recent suicide attempt that triggered the SOS team involvement for many participants was a sample characteristic that accounts for these findings.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Finally, it is notable that men made up more than one-fourth of this cohort of multimorbid individuals reporting IPV victimization, suicidality, and depression. These findings provide support for research involving men showing links between IPV victimization and suicidality [11,16] but are in contrast to the studies that found no link among men between suicidality and IPV victimization [14,15] and an inverse relationship between IPV and depression [15]. Perhaps the recent suicide attempt that triggered the SOS team involvement for many participants was a sample characteristic that accounts for these findings.…”
Section: Discussionsupporting
confidence: 61%
“…In fact, a previous systematic review showed that among women, IPV, suicide attempts, and depression were positively linked; however, among men, depression and IPV were associated in a negative direction, and there was no link between IPV and suicidality [15]. However, more recently, a South Korean study showed that past-year experiences of IPV were associated with suicidal ideation among both men and women [16]. There is also some evidence that IPV perpetration, as opposed to victimization, may be more associated with suicide among men.…”
Section: Introductionmentioning
confidence: 99%
“…Given the significance of marriage in one's life, especially in East Asian societies, it is not surprising that victims are often forced to endure abusive relationships. However, since IPV is an apparent crime that violates individual safety and human rights, victims should be provided with all possible protections (R. Kim et al 2022). Considering that victims of prolonged IPV are constantly affected in a way that undermines their psychological health, the most effective way to combat IPV is to adopt preventative measures or, at the very least, to enable them to seek protection as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Given the significance of marriage in one’s life, especially in East Asian societies, it is not surprising that victims are often forced to endure abusive relationships. However, since IPV is an apparent crime that violates individual safety and human rights, victims should be provided with all possible protections (R. Kim et al 2022).…”
Section: Discussionmentioning
confidence: 99%